Vikingdom : the blood eclipse - Yusry Abd Halim; Coyne, James; Shireen M.Hashim; Purcell, Dominic; Malthe, Natassia Linn; Fairbrass, Craig; Jon, Foo; Stevens, Conan; KRU Studios Sdn. Bhd. (Cyberjaya : KRU Studios Sdn. Bhd., 2013)
In the midst of time comes the clanging of steel against steel, a collision of myth, history and fiction....'Vikingdom'. Loosely based on Viking legends and the epic poems they left as record, with a creative interpretation,'Vikingdom' is a fantasy, action adventure about a forgotten king, Eirick, who was tasked with the impossible odds to defeat Thor, the God of Thunder. Thor is on a mission to gather the key ancient relics -'Mjolnir' - his hammer from Valhalla,'Necklace of Mary Magdalene' from Mitgard and the'Horn' from Helheim. This needs to be accomplished before the Blood Eclipse, which happens once every 800 years, failing which, the pagan Viking Gods will never be able to rule and conquer mankind ever again. Only one man can stop him... Eirick, the undead.
Executive producers, Norman A.Halim, Patrick Ewald ; director of photography, Eric Oh ; edited by Ezarisyirwan Basri ; music by Edry A. Halim
Dominic Purcell, Natassia Linn Malthe, Craig Fairbrass, Jon Foo, Conan Stevens.
DVD format.
In English with optional English, Malay and Mandarin subtitles.
Title from title screen.
Keywords: Action and adventure films; Fantasy films